On Forming Characteristics of Hems by Means of Incremental Sheet Forming - Dennis Steinfels; David Bailly (Journal of Manufacturing and Materials Processing, 2024)
Given the need for versatile joining processes, form-fit joining is gaining increasing importance. Although it has known limitations and complexity, roller hemming remains widely used due to its flexibility. Here, the novel Incremental Sheet Forming (ISF) hemming technique has the potential to expand the range of applications and process limits. It has already proven effective in preliminary works for joining comparatively small radii without wrinkles and cracks. However, a deeper understanding of the dominant material flow and deformation mechanism during forming is required to fully exploit its potential. This study aims to conduct a detailed examination of this technology through experimental and numerical investigations. Strain measurements on convex and concave hems provide insights into the material flow. A comparison of the forming mechanism for both processes is made using straight hems. The results show that ISF hemming has a favorable material flow for compensating cracks and wrinkles in curved hems. Additionally, it induces strains across the entire hem area, reaching higher values than those achieved with roller hemming. One reason for this is the forming mechanism, which combines tension, compression and shear, whereas roller hemming primarily involves bending and compression of the hemming radius.